Videoscape : an exhibition of video art. - Gale, Peggy (Toronto : Art Gallery of Ontario, 1974)
Askevold, David ; Cameron, Eric ; Campbell, Colin ; Cruise, Stephen ; Fitzgerald, Ed ; General Idea ; Goldberg, Michael ; Harding, Noel ; Levine, Les ; Morris, robert ; Murray, Ian ; Serra, Richard ; Steele, Lisa ; etc.
Videoscape an exhibition of video art, Art Gallery of Ontario, Toronto, Education and Extension, 20 November 1974 - 1 April 1975
English
kunstcatalogus